Implementation of the Independent Curriculum for PAUD School Readiness - Hariyani, Indaria Tri; Sulistiyani, Sulistiyani; Soemarmi, Soemarmi (UPI Kampus Cibiru, 2023)
The problem faced by PAUD teachers is that they are not ready for an independent curriculum policy that regulates education in Indonesia, especially in PAUD. Therefore, the purpose of this study is to help early childhood teachers implement the independent curriculum and deal with the policies in it. The method used a qualitative descriptive method, regarding real conditions and data that becomes information for researchers. This research was carried out at Pluz Az Zahra Pakal Islamic Kindergarten Surabaya on May 16, 17 and 18, 2023, through interviews and observations of the principal, curriculum representative, and all teachers. The results of this study indicate that the readiness carried out by the Pluz Az Zahra Islamic Kindergarten teacher in implementing the independent curriculum is quite ready, as evidenced by the ability and knowledge regarding the independent curriculum in the independent part. The impact of implementing an independent curriculum at the Pluz Az Zahra Islamic Kindergarten is that the learning process can be achieved and modified according to needs